2018
DOI: 10.1007/s00216-018-1415-x
|View full text |Cite
|
Sign up to set email alerts
|

Retention-time prediction in comprehensive two-dimensional gas chromatography to aid identification of unknown contaminants

Abstract: Comprehensive two-dimensional (2D) gas chromatography (GC×GC) coupled to mass spectrometry (MS, GC×GC-MS), which enhances selectivity compared to GC-MS analysis, can be used for non-directed analysis (non-target screening) of environmental samples. Additional tools that aid in identifying unknown compounds are needed to handle the large amount of data generated. These tools include retention indices for characterizing relative retention of compounds and prediction of such. In this study, two quantitative struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Even though these agents have been studies and examined in the literature. Regarding the peptide bond separation, the reverse phase ion-pair high-pressure liquid chromatography (HPLC) with the used of trifluoroacetic acid (TFA) as the mobile phase is usually used to serve as an alternative over the ion-exchange liquid chromatography [8].…”
Section: Introductionmentioning
confidence: 99%
“…Even though these agents have been studies and examined in the literature. Regarding the peptide bond separation, the reverse phase ion-pair high-pressure liquid chromatography (HPLC) with the used of trifluoroacetic acid (TFA) as the mobile phase is usually used to serve as an alternative over the ion-exchange liquid chromatography [8].…”
Section: Introductionmentioning
confidence: 99%
“…In reference [24], OV-17 SP (50% diphenyl 50% dimethyl siloxane) is also considered along with polar and non-polar SP. In reference [28], an accurate QSRR model for second dimension retention times and RI in two-dimensional GC was built. BPX50 (50% phenyl polysilphenylene siloxane) is used as a second dimension SP.…”
Section: Introductionmentioning
confidence: 99%
“…A data set with more than 800 compounds is published. The above-mentioned works [11,28] use proprietary ACD ChromGenius software for building an accurate QSRR model, and there are only sparse explanations of how exactly retention is predicted. Some works consider relatively large data sets consisting of compounds of very similar structures, e.g., polychlorinated biphenyls [29] and polybrominated diphenyl ethers [30].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, artificial-intelligence-based models have emerged as promising and reliable chemometric approaches in different studies. Veenaas et al [12] reported that the QSRR method could be used for the prediction of retention time, which can provide an insight into the separation mechanisms. The study stated that prediction of retention time is vital for decreasing the time needed to identify analytes and developing methods, particularly for nontargeted analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that L-M ANN outperformed all the other linear and nonlinear models. Similarly, Veenaas et al [12] reported that the QSRR method could be used for prediction of retention time (tR), which can provide an insight into the separation mechanisms. The study reported that the prediction oftR is vital for decreasing the time needed for analyte identification and method development, especially in nontargeted analysis.…”
Section: Introductionmentioning
confidence: 99%